Violence Against Women in the Film Women from Rote Island (Perempuan dari Pulau Rote) (2023) by Jeremias Nyangoen: Kekerasan terhadap Perempuan dalam Film Woman from Rote Island (Perempuan dari Pulau Rote) (2023) Karya Jeremias Nyangoen - Febrya Rusna Rizki Safira; Suseno (Universitas Negeri Semarang, 2025)
Gender violence that often occurs is violence against women. Women become the objects of violence because in society there is an assumption that women are weak creatures. The powerlessness of women is exploited by perpetrators to commit violence against women. Awareness of this ultimately makes women fight to free themselves. Film is a narrative work that, apart from functioning as a medium of entertainment, also functions as a reflection of social and cultural conditions in society. The aim of this research is to describe the forms of violence against women and women's struggle for justice in Jeremias Nyangoen’s film Women from Rote Island. This study is expected to provide a deep understanding of the representation of violence against women in film and to enrich the application of feminist literary criticism theory. The research method employed is descriptive qualitative with a feminist literary criticism approach. The primary data source for this study is the film Women from Rote Island. The results of the analysis show that the film complexly represents various forms of violence experienced by female characters, including physical, sexual, and psychological violence, while also highlighting various efforts by women to achieve justice. Kekerasan gender yang sering terjadi adalah kekerasan terhadap perempuan. Perempuan menjadi objek kekerasan karena dalam masyarakat terdapat anggapan bahwa perempuan adalah makhluk yang lemah. Ketidakberdayaan perempuan dimanfaatkan oleh pelaku untuk melakukan kekerasan terhadap perempuan. Kesadaran akan hal ini pada akhirnya membuat perempuan berjuang untuk membebaskan diri. Film merupakan karya naratif yang selain berfungsi sebagai media hiburan, juga berfungsi sebagai refleksi kondisi sosial dan budaya masyarakat. Tujuan penelitian ini adalah untuk mendeskripsikan bentuk-bentuk kekerasan terhadap perempuan dan perjuangan perempuan untuk mendapatkan keadilan dalam film Perempuan dari Pulau Rote karya Jeremias Nyangoen. Penelitian ini diharapkan dapat memberikan pemahaman yang mendalam tentang representasi kekerasan terhadap perempuan dalam film dan memperkaya penerapan teori kritik sastra feminis. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan kritik sastra feminis. Sumber data primer penelitian ini adalah film Perempuan dari Pulau Rote. Hasil analisis menunjukkan bahwa film tersebut secara kompleks merepresentasikan berbagai bentuk kekerasan yang dialami oleh tokoh perempuan, meliputi kekerasan fisik, seksual, dan psikis, sekaligus menyoroti berbagai upaya perempuan untuk mendapatkan keadilan.